Gainsharing: A review of theoretical perspectives and development of models - Gong, Yanlan (Auckland University of Technology, 2005)
The aim of this dissertation, completed for a Master of Business, is to firstly develop further theoretical insights on gainsharing. From these insights, the second aim is to provide New Zealand managers with a clear understanding of the underpinning concepts and practices to consider in the implementation of a gainshairing programme. This is done with a comprehensive literature review, from which research propositions are presented and related to three conceptual models: the fundamentals of gainsharing, the criteria to evaluate gainsharing effectiveness, and the factors influencing gainsharing effectiveness. In addition, four steps are recommended and several organisational factors are highlighted based on the models to guide an organisation in adopting a gainsharing programme. Finally, the major theoretical findings of the study are reviewed, as well as the limitations of the research and future research directions.
Keywords: Gain sharing